Historical and Social Aspects of Vaccination and the Anti-Vaccination Movement Worldwide: Influences on Serbia - Petković, Katarina М. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Infectious diseases have significantly shaped the course of human history. The earliest recorded pandemic was described during the Peloponnesian War in 430 BC. Since then, numerous smallpox, cholera, and influenza epidemics have been recorded, including the 20th and 21st centuries. This year marks the 228th anniversary of the use of the Jenner smallpox vaccine. For nearly two centuries, vaccines have protected people from infectious diseases and, alongside improved hygiene measures, contributed to a higher quality of life. Despite the well-documented benefits of immunization, vaccine-preventable diseases continue to pose a global threat.In Serbia, compulsory immunization was introduced as early as 1839, establishing a long-standing tradition of vaccination and domestic vaccine production. In more recent history, Serbia was among the first countries to implement vaccines against whooping cough, mumps, and measles, as well as hepatitis B for at-risk populations.The anti-vaccine movement employs various strategies to persuade the public that vaccines are unsafe, casting doubt on their quality and on the intentions of those advocating for their use. Globally, anti-vaccine activism fosters vaccine hesitancy or outright refusal, thereby undermining efforts to halt and eradicate infectious diseases. This resistance complicates epidemiological conditions and results in avoidable illnesses and, in some cases, fatalities from diseases that are preventable through safe and effective vaccination. Effective communication is essential to the success of public health interventions, and citizens’ trust in science and the healthcare system must be restored and strengthened.
Keywords: Serbia; history of vaccination; anti-vaccination movement; public health